2012
DOI: 10.1371/journal.pone.0045085
|View full text |Cite
|
Sign up to set email alerts
|

Dia-Interacting Protein (DIP) Imposes Migratory Plasticity in mDia2-Dependent Tumor Cells in Three-Dimensional Matrices

Abstract: Tumor cells rely upon membrane pliancy to escape primary lesions and invade secondary metastatic sites. This process relies upon localized assembly and disassembly cycles of F-actin that support and underlie the plasma membrane. Dynamic actin generates both spear-like and bleb structures respectively characterizing mesenchymal and amoeboid motility programs utilized by metastatic cells in three-dimensional matrices. The molecular mechanism and physiological trigger(s) driving membrane plasticity are poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 63 publications
(94 reference statements)
3
30
1
Order By: Relevance
“…We previously showed CXCL12 initiates mDia2-dependent non-apoptotic blebbing in MDA-MB-231 cells in 2D matrices and within 3D collagen gels, and causes cells to adopt an elongated phenotype[11]. This resembled phenotypes observed upon treatment with a functional mDia FH2 domain inhibitor, SMIFH2.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…We previously showed CXCL12 initiates mDia2-dependent non-apoptotic blebbing in MDA-MB-231 cells in 2D matrices and within 3D collagen gels, and causes cells to adopt an elongated phenotype[11]. This resembled phenotypes observed upon treatment with a functional mDia FH2 domain inhibitor, SMIFH2.…”
Section: Resultsmentioning
confidence: 90%
“…1B). CXCL12 initiated blebbing within an hour of treatment [11], with mDia2 and CXCR4 distinctly localizing in blebs at the cell periphery (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of the Formin-like protein 2 evokes MAT,78 and FHOD1 promotes membrane blebbing in conjunction with ROCK1 and Src79, while Dia1 promotes bleb-based cell motility through the GEF LARG 80. Eisenmann and colleagues demonstrated that inhibition of mDia2, through binding to DIA-interacting protein (DIP), similarly induces an amoeboid transition 8182. Interestingly, the DIAPH3 locus encodes multiple splice variants that differentially impact actin dynamics and membrane blebbing 83.…”
Section: Pathways Mediating the Amoeboid Phenotypementioning
confidence: 99%